Brown planthopper E78 regulates moulting and ovarian development by interacting with E93 - Shi-wen ZHENG; Xiao-juan JIANG; Yi-wen MAO; Yan LI; Han GAO; Xin-da LIN (Journal of Integrative Agriculture, 2023)
The brown planthopper (Nilaparvata lugens) is the main migratory pest in many rice growing areas in Asia. E78 is a member of the nuclear hormone receptor superfamily which plays an important role in egg development and maternal regulation of early embryogenesis. In this study, brown planthopper E78 (NlE78) was cloned, and the predicted amino acid sequence showed that it contains two conserved domains: NR-LBD and DBD. qRT-PCR showed that the expression of NlE78 is high in the fifth instar nymphs and the ovaries of females. After downregulation of NlE78, the rate of moulting failure (33.2%) increased significantly, and ovarian development was delayed. However, when NlE78 was downregulated together with NlE93, the emergence rate increased significantly (78.79%), and ovarian development was similar to that when NlE78 was downregulated but not delayed. A co-immunoprecipitation experiment showed that NlE78 interacts with NlE93, a crucial downstream transcription factor of the ecdysone signalling pathway. Cellular localization by immunofluorescence revealed that NlE78 and NlE93 are expressed in the nucleus. This study indicates that NlE78 regulates ovarian development and moulting, possibly through its interaction with NlE93. This study is of great significance for the development of new pesticides and control methods based on newly discovered targets.